1995
DOI: 10.1080/02724936.1995.11747749
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response in bacterial meningitis: cytokine levels in the cerebrospinal fluid

Abstract: Inflammatory response plays an important role in the pathogenesis of cerebral injury in bacterial meningitis. In this study, we evaluated the cytokine levels of interleukin 1-beta (IL1 beta), tumour necrosis factor alpha (TNF alpha) and interleukin 6 (IL6) in the cerebrospinal fluid (CSF), and determined their correlation with acute clinical complications and with changes in CSF biochemistry. Interleukin 6, TNF alpha and IL1 beta were present in 9/9, 3/9 and 4/9 patients, respectively. The CSFs with detectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Similar results were obtained in studies of infants, older children and adults 6,18,19 . According to Dulkerian et al 20 , young infants respond to the bacterial invasion of the CNS with the release of cytokines at comparable levels to those observed in older children and adults.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results were obtained in studies of infants, older children and adults 6,18,19 . According to Dulkerian et al 20 , young infants respond to the bacterial invasion of the CNS with the release of cytokines at comparable levels to those observed in older children and adults.…”
Section: Discussionsupporting
confidence: 76%
“…In spite of the mortality in our study being relatively low, the frequency of serious complications was high, demonstrating the need to develop methods of early detection and evaluation of the clinical course of the disease. Low et al 18 observed a correlation between the simultaneous presence of TNF-α, IL-1β and IL-6 in the CSF, with low values of glucose in five children with meningitis, and between the detection of TNF-α or IL-1β in the CSF and the duration of fever, convulsions, spasticity and death. McCracken et al 8 verified a relationship between levels of IL-1β in CSF of over 200 pg/ml and the number of days in which endotoxin, antigen K 1 and bacteria persisted in 42 neonates with meningitis due to enterobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiologic sequelae of meningitis that result from the interaction between the bacteria and the host constitute a complex cascade (Tsao et al, 1999). The presence of cytokines, such as TNF-α, IL-1β, and IL-6 in the CSF, and blood are hallmarks of the pathogenesis of neonatal meningitis (Low et al, 1995). IL-1β was first related to meningeal inflammation when it was shown that intracisternal administration of homologous IL-1β in rabbit's increased CSF white blood cell counts (Ramilo et al, 1990).…”
mentioning
confidence: 99%
“…TNF-α may also influence transport of compounds into the brain by "opening" the blood-brain barrier (BBB) [62]. In patients with bacterial meningitis, high TNF-α levels in the CSF correlate with increased levels of IL-6 and total protein, as well as low glucose levels [63]. In addition, elevated TNF-α and IL-1β levels in the cerebrospinal fluid are associated with prolonged fever, seizures, spasticity, and death in meningitis [63][64][65].…”
Section: Colony Stimulating Factorsmentioning
confidence: 99%